Broadband-gap perovskite solar cell modified by buried bottom interface and preparation method of wide-band-gap perovskite solar cell
By chromatography of amide oxime compounds between the hole transport layer and the perovskite absorption layer of a wide bandgap perovskite solar cell, the problem of serious non-radiation loss at the interface is solved, and the photoelectric conversion efficiency and stability of the solar cell are improved.
Patent Information
- Application Number
- CN202411949061.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In wide-bandgap perovskite solar cells, the interface non-radiation loss between the perovskite absorber layer and the hole transport layer is severe, resulting in poor interface transmission quality and low filling factor, affecting the performance and stability of the solar cell.
The buried interface modification technology is used to improve the interface characteristics by chromatography of amide oxime compounds between the hole transport layer and the perovskite absorption layer as the buried interface modification layer.
Through interface modification, the hydrophobicity of the hole transport layer is improved, the crystallization and growth of the perovskite layer is promoted, the interface defects are reduced, and the photoelectric conversion efficiency and device stability are improved.
Smart Images

Figure CN119789671A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a buried interface modified wide bandgap perovskite solar cell and a preparation method thereof. Background Art
[0002] Wide-bandgap perovskite solar cells are a new type of solar cell based on perovskite structural materials, which have the advantages of high efficiency, low cost and easy processing. The structure of this solar cell usually has multiple functional layers stacked from bottom to top, including a conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer, a buffer layer and a metal electrode layer. Among them, the perovskite absorption layer is the core part of the solar cell, responsible for absorbing sunlight and generating photogenerated carriers. The wide-bandgap perovskite solar cell has attracted widespread attention because it has a high open-circuit voltage and short-circuit current, which is expected to achieve a high photoelectric conversion efficiency. In addition, perovskite materials also have rich elemental composition and tunable band gap, which provides a broad space for optimizing the performance of solar cells.
[0003] Although wide-bandgap perovskite solar cells have many advantages, there are still some defects that need to be solved urgently. The interface stability between the perovskite material and the adjacent functional layer is one of the key factors affecting the long-term performance of solar cells. Chemical reactions, element diffusion or interface defects at the interface may lead to an increase in the carrier recombination rate. At the same time, the carrier transmission efficiency between the perovskite absorption layer and the adjacent functional layer will also directly affect the performance of the solar cell. Energy level mismatch or transmission barriers at the interface may lead to carrier loss and reduce the photoelectric conversion efficiency.
[0004] To solve such problems, the existing technology often uses interface modifiers to modify the interface of wide-bandgap perovskite solar cells to improve device performance and stability; however, interface modifiers are often used between the wide-bandgap perovskite absorption layer and the electron transport layer, and their effects are mostly concentrated on reducing the wide-bandgap perovskite opening voltage loss. However, there is still serious interface non-radiative recombination at the interface between the wide-bandgap perovskite absorption layer and the hole transport layer, and its interface transmission quality is poor and the filling factor is low, resulting in poor performance and stability of wide-bandgap perovskite solar cells. How to solve such problems and prepare high-performance and stable wide-bandgap perovskite solar cells is one of the technical problems that still need to be solved. Summary of the invention
[0005] The problem to be solved by the present invention is to provide a wide bandgap perovskite solar cell with a buried interface modification and a preparation method thereof, so as to solve the problem of serious non-radiative loss at the interface between the perovskite absorption layer and the hole transport layer and poor interface transmission quality in the wide bandgap perovskite solar cell.
[0006] The technical solution adopted to solve the technical problem is to provide a wide bandgap perovskite solar cell with a buried interface modification, wherein the wide bandgap perovskite solar cell with a buried interface modification comprises a conductive substrate, a hole transport layer, a buried interface modification layer, a wide bandgap perovskite absorption layer, a rear interface modification layer, an electron transport layer, a buffer layer and a metal electrode layer which are sequentially stacked from bottom to top; The material of the buried bottom interface modification layer is amide oxime compound.
[0007] The beneficial effects of the technical solution adopted in the present invention are as follows: the present invention focuses on the interface modification at the buried interface, performs buried interface modification between the hole transport layer and the wide band gap perovskite absorption layer of the wide band gap perovskite solar cell, and after modification with amide oxime compounds, the surface hydrophobicity of the hole transport layer is enhanced, which is beneficial to the crystallization and growth of the perovskite layer. After modification, the defects at the buried interface are reduced, hole extraction is promoted, non-radiative recombination is reduced, and the filling factor and photoelectric conversion efficiency of the solar cell are improved; at the same time, the amide oxime compounds can form hydrogen bonds and are tightly combined with the hole transport layer, thereby improving the charge transfer efficiency and stability of the interface; in addition, the amide oxime compounds have -NH 2 groups, further improving the growth quality of perovskite films and battery stability.
[0008] Preferably, the amide oxime compound is (Z)-4-fluorobenzamide oxime.
[0009] The beneficial effects of the above technical solution of the present invention are as follows: the oxime group (-C=NOH) in the (Z)-4-fluorobenzamide oxime molecule gives it unique reactivity and interface modification ability. These groups can interact with specific sites in the perovskite material, thereby affecting the growth process and final quality of the perovskite film; the amino group can provide free electron pairs to interact with the uncoordinated Pb in the wide bandgap perovskite. 2+ Form coordination bonds and regulate film crystallization.
[0010] Preferably, the conductive substrate is made of ITO conductive glass; the hole transport layer is made of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid; the wide bandgap perovskite absorption layer is made of Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 ; The material of the rear interface modification layer is 1,3-diaminopropane dihydroiodide; the material of the electron transport layer is C 60 The material of the buffer layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; the material of the metal electrode layer is copper metal.
[0011] The present invention also provides a method for preparing the above-mentioned buried interface modified wide bandgap perovskite solar cell, comprising the following steps: (1) spin coating a hole transport layer solution on a pre-cleaned conductive substrate and annealing to obtain a hole transport layer; the hole transport layer solution is an organic solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid; (2) dissolving an amide oxime compound in an organic solvent to obtain a buried bottom interface treatment solution; (3) spin coating the buried interface treatment solution on the hole transport layer and annealing to obtain a buried interface modification layer; (4) Spin coating a wide bandgap perovskite precursor solution on the buried interface modification layer by an anti-solvent method and annealing to obtain a wide bandgap perovskite absorption layer; the wide bandgap perovskite precursor solution is Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 of organic solution; (5) spin coating a rear interface treatment solution on the wide bandgap perovskite absorption layer and annealing to obtain a rear interface modification layer; the rear interface treatment solution is an organic solution of 1,3-diaminopropane dihydroiodide; (6) An electron transport layer, a buffer layer and a metal electrode layer are sequentially deposited on the surface of the rear interface modification layer by a thermal evaporation method.
[0012] Preferably, the organic solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid in step (1) is an ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid with a mass concentration of 0.3-0.8 mg / mL; the spin coating speed in step (1) is 2500-3500 rpm, and the time is 10-20 s; the annealing temperature is 90-110°C, and the time is 8-12 min.
[0013] More preferably, the organic solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid in step (1) is an ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid with a mass concentration of 0.5 mg / mL; the spin coating speed in step (1) is 3000 rpm and the time is 20 s; the annealing temperature is 100°C and the time is 10 min.
[0014] Preferably, the organic solvent in step (2) is isopropanol; and the mass concentration of the buried interface treatment solution is 0.5-2 mg / mL.
[0015] More preferably, the mass concentration of the buried interface treatment solution is 1 mg / mL.
[0016] Preferably, in step (3), the spin coating speed is 3500-4500 rpm, and the time is 20-30 s; the annealing temperature is 50-70° C., and the time is 4-6 min.
[0017] More preferably, in step (3), the spin coating speed is 4000 rpm, and the time is 30 s; and the annealing temperature is 60° C., and the time is 5 min.
[0018] Preferably, step (4) comprises the following steps: adding a wide bandgap perovskite precursor solution onto the buried interface modification layer, performing a first step spin coating at 400-600 rpm for 1-3 s, then performing a second step spin coating at 3000-4000 rpm for 30-50 s, and adding diethyl carbonate at 15-20 s of the second step spin coating; after the spin coating is completed, placing the layer at 50-70°C for a first step annealing for 1-3 min, and then placing the layer at 90-110°C for a second step annealing for 4-6 min.
[0019] More preferably, step (4) comprises the following steps: adding a wide bandgap perovskite precursor solution onto the buried interface modification layer, performing a first step spin coating at 500 rpm for 2 s, then performing a second step spin coating at 4000 rpm for 40 s, and adding diethyl carbonate at 20 s of the second step spin coating; after the spin coating is completed, placing it at 60°C for a first step annealing for 2 min, and then placing it at 100°C for a second step annealing for 5 min.
[0020] Preferably, the organic solution of 1,3-diaminopropane dihydroiodide in step (5) is an isopropanol solution of 1,3-diaminopropane dihydroiodide with a mass concentration of 0.5-2 mg / mL; the spin coating speed in step (5) is 2000-4000 rpm, and the time is 20-40 s; the annealing temperature is 90-110°C, and the time is 4-6 min.
[0021] Preferably, the organic solution of 1,3-diaminopropane dihydroiodide in step (5) is an isopropanol solution of 1,3-diaminopropane dihydroiodide with a mass concentration of 1 mg / mL; the spin coating speed in step (5) is 3000 rpm and the time is 30 s; the annealing temperature is 100° C. and the time is 5 min.
[0022] Preferably, in step (6), the deposition rate is 0.05-0.2 Å / s; the electron transport layer deposition thickness is 15-25 nm, the buffer layer deposition thickness is 4-6 nm, and the metal electrode layer deposition thickness is 90-110 nm.
[0023] More preferably, in step (6), the deposition rate is 0.1 Å / s; the electron transport layer deposition thickness is 20 nm, the buffer layer deposition thickness is 5 nm, and the metal electrode layer deposition thickness is 100 nm.
[0024] The present invention has the following beneficial effects: (1) The buried interface modified wide bandgap perovskite solar cell prepared by the present invention performs interface modification on the buried interface, focusing on improving the interface transmission quality and filling factor. The surface hydrophobicity of the hole transport layer after the buried interface modification is increased, which is conducive to the high-quality growth of the perovskite film and solves the problem of poor device stability. (2) The buried interface modified wide bandgap perovskite solar cell prepared by the present invention has few interface defects in the hole transport layer / wide bandgap perovskite absorption layer, performs well in terms of non-radiative loss and charge transfer loss, and has a high photoelectric conversion efficiency, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the structure of a wide bandgap perovskite solar cell with buried interface modification prepared by the present invention; Figure 2 The wide bandgap perovskite solar cell with buried interface modification prepared in Example 1 and Comparative Example 1 JV Graphs; Figure 3 is the light intensity of the wide bandgap perovskite solar cell with buried interface modification prepared in Example 1 and Comparative Example 1 - V OC Survey drawings; Figure 4 It is an EQE curve diagram of the buried interface modified wide bandgap perovskite solar cell prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0026] The principles and features of the present invention are described below in conjunction with the examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. (Z)-4-Fluorobenzamide oxime, from Bid Pharmaceuticals, CAS is 69113-32-2; 1,3-diaminopropane dihydroiodide, from Xi'an Baolait, CAS is 120675-53-8; [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid, CAS is 2882156-63-8.
[0027] Example 1 A wide bandgap perovskite solar cell with a buried bottom interface modification, the wide bandgap perovskite solar cell with a buried bottom interface modification comprising a conductive substrate made of ITO conductive glass, a hole transport layer made of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid, a buried bottom interface modification layer made of (Z)-4-fluorobenzamide oxime, and a Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 The wide bandgap perovskite absorption layer, the rear interface modification layer made of 1,3-diaminopropane dihydroiodide, and the C 60 An electron transport layer, a buffer layer made of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, and a metal electrode layer made of copper metal; The device structure of the wide-bandgap perovskite solar cell with buried interface modification is as follows: Figure 1 shown.
[0028] The wide bandgap perovskite solar cell with buried interface modification in this embodiment is prepared by the following steps: (1) Pre-clean the 25 mm × 25 mm ITO conductive glass with ultrapure water and ethanol for 20 min, dry it on a warm bench, and place it under UV-O 3 Treat in atmosphere for 20 min; (2) Spin coating a 0.5 mg / mL ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid on the pre-cleaned ITO conductive glass at a spin coating speed of 3000 rpm for 20 s, and then annealing at 100° C. for 10 min to obtain a hole transport layer; (3) dissolving (Z)-4-fluorobenzamide oxime in isopropanol so that the mass concentration of (Z)-4-fluorobenzamide oxime in isopropanol is 1 mg / mL, thereby obtaining a buried bottom interface treatment solution; (4) Spin coating the buried interface treatment solution on the surface of the cooled hole transport layer at a spin coating speed of 4000 rpm for 20 s, and then annealing at 60° C. for 5 min to obtain a buried interface modification layer; (5) CsI, FAI, PbBr 2 、PbI 2 Press Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 The proportion of 20% was weighed and dissolved in a mixed solution of dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to obtain a component Cs 0.2 FA0.8 Pb(I 0.6 Br 0.4 ) 3 A wide bandgap perovskite precursor solution of 1.77 eV; (6) adding a wide bandgap perovskite precursor solution to the surface of the buried interface modification layer, performing the first step of spin coating at a spin coating speed of 500 rpm for 2 s, and then performing the second step of spin coating at a spin coating speed of 4000 rpm for 40 s, adding diethyl carbonate at 20 s of the second step of spin coating, placing the first step of annealing at 60°C for 2 min after the spin coating, and then placing the second step of annealing at 100°C for 5 min to obtain a wide bandgap perovskite absorption layer; (7) dissolving 1,3-diaminopropane dihydroiodide in isopropanol to make the mass concentration of 1,3-diaminopropane dihydroiodide be 1 mg / mL to obtain a post-interface treatment solution; (8) Spin coating the rear interface treatment solution on the surface of the wide bandgap perovskite absorption layer at a spin coating speed of 3000 rpm for 30 s, and then annealing at 100° C. for 5 min to obtain a rear interface modification layer; (9) Heating C by thermal evaporation 60 To 530℃, C 60 The evaporation rate is 0.1 Å / s until C 60 The thickness of the deposition on the rear interface modification layer is 20 nm to obtain the electron transport layer; (10) heating 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline to a temperature of 100° C. by an atomic deposition method, so that the evaporation rate of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline is 0.1 Å / s, until the deposition thickness of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline on the electron transport layer is 5 nm, thereby obtaining a buffer layer; (11) The metallic copper is heated by thermal evaporation method with an evaporation rate of 0.1 Å / s until the deposition thickness of the metallic copper on the buffer layer is 100 nm, thereby obtaining a wide bandgap perovskite solar cell with buried interface modification.
[0029] Example 2 A buried interface modified wide bandgap perovskite solar cell, whose structure and material are the same as those in Example 1.
[0030] The wide bandgap perovskite solar cell with buried interface modification in this embodiment is prepared by the following steps: (1) Pre-clean the 25 mm × 25 mm ITO conductive glass with ultrapure water and ethanol for 20 min, dry it on a warm bench, and place it under UV-O 3 Treat in atmosphere for 20 min; (2) Spin coating a 0.3 mg / mL ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid on the pre-cleaned ITO conductive glass at a spin coating speed of 2500 rpm for 10 s, and then annealing at 90°C for 8 min to obtain a hole transport layer; (3) dissolving (Z)-4-fluorobenzamide oxime in isopropanol so that the mass concentration of (Z)-4-fluorobenzamide oxime in isopropanol is 0.5 mg / mL, thereby obtaining a buried bottom interface treatment solution; (4) Spin coating the buried interface treatment solution on the surface of the cooled hole transport layer at a spin coating speed of 3500 rpm for 20 s, and then annealing at 50° C. for 4 min to obtain a buried interface modification layer; (5) CsI, FAI, PbBr 2 、PbI 2 Press Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 The proportion of 20% was weighed and dissolved in a mixed solution of dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to obtain a component Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 A wide bandgap perovskite precursor solution of 1.77 eV; (6) adding a wide bandgap perovskite precursor solution to the surface of the buried interface modification layer, performing the first step of spin coating at a spin coating speed of 400 rpm for 1 s, and then performing the second step of spin coating at a spin coating speed of 3000 rpm for 30 s, adding diethyl carbonate at 15 s of the second step of spin coating, placing the first step of annealing at 50°C for 1 min, and then placing the second step of annealing at 90°C for 4 min to obtain a wide bandgap perovskite absorption layer; (7) dissolving 1,3-diaminopropane dihydroiodide in isopropanol to make the mass concentration of 1,3-diaminopropane dihydroiodide be 0.5 mg / mL to obtain a post-interface treatment solution; (8) Spin coating the rear interface treatment solution on the surface of the wide bandgap perovskite absorption layer at a spin coating speed of 2000 rpm for 20 s, and then annealing at 90° C. for 4 min to obtain a rear interface modification layer; (9) Heating C by thermal evaporation 60 To 530℃, C 60 The evaporation rate is 0.05 Å / s until C 60The thickness of the deposition on the rear interface modification layer is 15 nm to obtain the electron transport layer; (10) heating 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline to a temperature of 100° C. by an atomic deposition method, so that the evaporation rate of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline is 0.05 Å / s, until the deposition thickness of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline on the electron transport layer is 4 nm, thereby obtaining a buffer layer; (11) The metallic copper is heated by thermal evaporation method with an evaporation rate of 0.05 Å / s until the deposition thickness of the metallic copper on the buffer layer is 90 nm, thereby obtaining a wide bandgap perovskite solar cell with buried interface modification.
[0031] Example 3 A buried interface modified wide bandgap perovskite solar cell, whose structure and material are the same as those in Example 1.
[0032] The wide bandgap perovskite solar cell with buried interface modification in this embodiment is prepared by the following steps: (1) Pre-clean the 25 mm × 25 mm ITO conductive glass with ultrapure water and ethanol for 20 min, dry it on a warm bench, and place it under UV-O 3 Treat in atmosphere for 20 min; (2) Spin coating a 0.8 mg / mL ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid on the pre-cleaned ITO conductive glass at a spin coating speed of 3500 rpm for 20 s, and then annealing at 110°C for 12 min to obtain a hole transport layer; (3) dissolving (Z)-4-fluorobenzamide oxime in isopropanol so that the mass concentration of (Z)-4-fluorobenzamide oxime in isopropanol is 2 mg / mL, thereby obtaining a buried bottom interface treatment solution; (4) Spin coating the buried interface treatment solution on the surface of the cooled hole transport layer at a spin coating speed of 4500 rpm for 30 s, and then annealing at 70° C. for 6 min to obtain a buried interface modification layer; (5) CsI, FAI, PbBr 2 、PbI 2 Press Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 The proportion of 20% was weighed and dissolved in a mixed solution of dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to obtain a component Cs 0.2 FA 0.8 Pb(I0.6 Br 0.4 ) 3 A wide bandgap perovskite precursor solution of 1.77 eV; (6) adding a wide bandgap perovskite precursor solution to the surface of the buried interface modification layer, performing the first step of spin coating at a spin coating speed of 600 rpm for 3 s, and then performing the second step of spin coating at a spin coating speed of 4000 rpm for 50 s, adding diethyl carbonate at 20 s of the second step of spin coating, placing the first step of annealing at 70°C for 3 min, and then placing the second step of annealing at 110°C for 6 min, to obtain a wide bandgap perovskite absorption layer; (7) dissolving 1,3-diaminopropane dihydroiodide in isopropanol to make the mass concentration of 1,3-diaminopropane dihydroiodide be 2 mg / mL, to obtain a post-interface treatment solution; (8) Spin coating the rear interface treatment solution on the surface of the wide bandgap perovskite absorber layer at a spin coating speed of 4000 rpm for 40 s, and then annealing at 110° C. for 6 min to obtain a rear interface modification layer; (9) Heating C by thermal evaporation 60 To 530℃, C 60 The evaporation rate is 0.2 Å / s until C 60 The thickness of the deposition on the rear interface modification layer is 25 nm to obtain the electron transport layer; (10) heating 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline to a temperature of 100° C. by an atomic deposition method, so that the evaporation rate of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline is 0.2 Å / s, until the deposition thickness of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline on the electron transport layer is 6 nm, thereby obtaining a buffer layer; (11) The metallic copper is heated by thermal evaporation method with an evaporation rate of 0.2 Å / s until the deposition thickness of the metallic copper on the buffer layer is 110 nm, thereby obtaining a wide bandgap perovskite solar cell with buried interface modification.
[0033] Comparative Example 1 A wide bandgap perovskite solar cell, the wide bandgap perovskite solar cell comprising a conductive substrate made of ITO conductive glass, a hole transport layer made of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid, and a Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 The wide bandgap perovskite absorption layer, the rear interface modification layer made of 1,3-diaminopropane dihydroiodide, and the C 60An electron transport layer, a buffer layer made of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, and a metal electrode layer made of copper metal; The wide bandgap perovskite solar cell in this comparative example is prepared by the following steps: (1) Pre-clean the 25 mm × 25 mm ITO conductive glass with ultrapure water and ethanol for 20 min, dry it on a warm bench, and place it under UV-O 3 Treat in atmosphere for 20 min; (2) Spin coating a 0.5 mg / mL ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid on the pre-cleaned ITO conductive glass at a spin coating speed of 3000 rpm for 20 s, and then annealing at 100° C. for 10 min to obtain a hole transport layer; (3) CsI, FAI, PbBr 2 、PbI 2 Press Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 The proportion of 20% was weighed and dissolved in a mixed solution of dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to obtain a component Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 ) 3 A wide bandgap perovskite precursor solution of 1.77 eV; (4) adding a wide bandgap perovskite precursor solution to the surface of the hole transport layer, performing the first step of spin coating at a spin coating speed of 500 rpm for 2 s, and then performing the second step of spin coating at a spin coating speed of 4000 rpm for 40 s, adding diethyl carbonate at 20 s of the second step of spin coating, placing the first step of annealing at 60°C for 2 min after the spin coating, and then placing the second step of annealing at 100°C for 5 min to obtain a wide bandgap perovskite absorption layer; (5) dissolving 1,3-diaminopropane dihydroiodide in isopropanol to make the mass concentration of 1,3-diaminopropane dihydroiodide be 1 mg / mL to obtain a post-interface treatment solution; (6) Spin coating the rear interface treatment solution on the surface of the wide bandgap perovskite absorption layer at a spin coating speed of 3000 rpm for 30 s, and then annealing at 100° C. for 5 min to obtain a rear interface modification layer; (7) Heating C by thermal evaporation 60 To 530℃, C 60 The evaporation rate is 0.1 Å / s until C 60The thickness of the deposition on the rear interface modification layer is 20 nm to obtain the electron transport layer; (8) heating 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline to a temperature of 100° C. by an atomic deposition method, so that the evaporation rate of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline is 0.1 Å / s, until the deposition thickness of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline on the electron transport layer is 5 nm, thereby obtaining a buffer layer; (9) The metallic copper is heated by thermal evaporation at a rate of 0.1 Å / s until the deposition thickness of the metallic copper on the buffer layer is 100 nm, thereby obtaining a wide bandgap perovskite solar cell.
[0034] Experimental example The wide bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 were subjected to JV The curve test was carried out as follows: In a glove box filled with nitrogen, a Keysight B2901A source meter was used at AM 1.5G (100 mW cm −2 ) light source (Enlitech, SS-F5); the light intensity was calibrated by a silicon reference cell (SRC-00205, Enlitech); JV The scan rate of the measurement was 100 mV·s -1 , delay time is 50 ms, voltage step size is 10 mV; the active area of all devices is 0.0576 cm 2 ; Test results such as Figure 2~3 shown.
[0035] pass Figure 2 It can be seen that the wide bandgap perovskite solar cell with buried interface modification prepared in Example 1 of the present invention has V OC The improvement is mainly based on the significant reduction of non-radiative recombination at the wide bandgap perovskite buried interface, the reduction of interface defects, and the improvement of quality. V OC ( Figure 3 ) It can be seen that the ideal factors n of the wide bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 are 1.59 and 1.81, respectively; this shows that the buried interface modified wide bandgap perovskite solar cell prepared in the present invention has been improved in terms of non-radiative loss and charge transfer loss.
[0036] 2. The wide bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 were subjected to EQE curve testing. The specific method is as follows: the spectral response was recorded under monochromatic light from 300 nm to 800 nm with a step of 10 nm and a chopping frequency of 210 Hz using a solar cell quantum efficiency measurement system (QE-R, Enlitech). The results are shown in FIG. Figure 4 shown.
[0037] from Figure 4 It can be seen that the spectral response of the wide bandgap perovskite solar cell with buried interface modification prepared in Example 1 of the present invention is better than that of the comparative example, which is undoubtedly due to the short-circuit current density ( J SC ) is the main reason for the increase. The increase in short-circuit current density indicates that the battery has a higher photoelectric conversion efficiency.
[0038] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.
Claims
1. A buried interface modified wide bandgap perovskite solar cell, characterized in that: The buried interface modified wide bandgap perovskite solar cell comprises a conductive substrate, a hole transport layer, a buried interface modification layer, a wide bandgap perovskite absorption layer, a rear interface modification layer, an electron transport layer, a buffer layer and a metal electrode layer which are stacked in sequence from bottom to top; The material of the buried interface modification layer is amide oxime compound.
2. The wide bandgap perovskite solar cell with buried interface modification according to claim 1, characterized in that: The amide oxime compound is (Z)-4-fluorobenzamide oxime.
3. The wide bandgap perovskite solar cell with buried interface modification according to claim 1, characterized in that: The conductive substrate is made of ITO conductive glass; the hole transport layer is made of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid; the wide bandgap perovskite absorption layer is made of Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3; the material of the rear interface modification layer is 1,3-diaminopropane dihydroiodide; the material of the electron transport layer is C 60 The material of the buffer layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; the material of the metal electrode layer is copper metal.
4. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) spin coating a hole transport layer solution on a pre-cleaned conductive substrate and annealing to obtain a hole transport layer; the hole transport layer solution is an organic solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid; (2) dissolving an amide oxime compound in an organic solvent to obtain a buried bottom interface treatment solution; (3) spin coating the buried interface treatment solution on the hole transport layer and annealing to obtain a buried interface modification layer; (4) spin coating a wide bandgap perovskite precursor solution on the buried interface modification layer by an anti-solvent method and annealing to obtain a wide bandgap perovskite absorption layer; the wide bandgap perovskite precursor solution is Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 organic solution; (5) spin coating a rear interface treatment solution on the wide bandgap perovskite absorption layer and annealing to obtain a rear interface modification layer; the rear interface treatment solution is an organic solution of 1,3-diaminopropane dihydroiodide; (6) An electron transport layer, a buffer layer and a metal electrode layer are sequentially deposited on the surface of the rear interface modification layer by a thermal evaporation method.
5. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to claim 4, characterized in that: The organic solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid in step (1) is an ethanol solution of [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid with a mass concentration of 0.3-0.8 mg / mL; the spin coating speed in step (1) is 2500-3500 rpm, and the time is 10-20 s; the annealing temperature is 90-110° C., and the time is 8-12 min.
6. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to claim 4, characterized in that: The organic solvent in step (2) is isopropanol; the mass concentration of the buried interface treatment solution is 0.5-2 mg / mL.
7. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to claim 4, characterized in that: In the step (3), the spin coating speed is 3500-4500 rpm, and the time is 20-30 s; the annealing temperature is 50-70° C., and the time is 4-6 min.
8. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to claim 4, characterized in that: The step (4) comprises the following steps: dripping a wide bandgap perovskite precursor solution onto the buried interface modification layer, performing a first step spin coating at 400-600 rpm for 1-3 s, then performing a second step spin coating at 3000-4000 rpm for 30-50 s, and dripping diethyl carbonate at 15-20 s of the second step spin coating; after the spin coating is completed, placing the layer at 50-70°C for a first step annealing for 1-3 min, and then placing the layer at 90-110°C for a second step annealing for 4-6 min.
9. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to claim 4, characterized in that: The organic solution of 1,3-diaminopropane dihydroiodide in step (5) is an isopropanol solution of 1,3-diaminopropane dihydroiodide with a mass concentration of 0.5-2 mg / mL; the spin coating speed in step (5) is 2000-4000 rpm, and the time is 20-40 s; the annealing temperature is 90-110° C., and the time is 4-6 min.
10. The method for preparing a wide bandgap perovskite solar cell with buried interface modification according to claim 4, characterized in that: The deposition rate in step (6) is 0.05-0.2 Å / s; the deposition thickness of the electron transport layer is 15-25 nm, the deposition thickness of the buffer layer is 4-6 nm, and the deposition thickness of the metal electrode layer is 90-110 nm.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN115295727A
Buried interface modified perovskite solar cell module and preparation method thereof
CN118139435A
Broadband-gap perovskite solar cell and preparation method thereof
CN118284073A
Perovskite solar cell provided with an adsorbent material for adsorbing toxic materials
US20230088203A1
Halide perovskite solar cell and bottom interface self-growth modification method therefor
WO2023155562A1
Cited By
Perovskite battery containing multiple modification layers and preparation method thereof
CN120692993A